(Study On The Of Rotation Mollen Dryer and Comparison Sugar and Noni pulp on the Characteristic of Noni Juice Microencapsulation (Morinda citrifolia) - Indra Neffi Ridwan; H G Pohan; Yudi Iswahyudi; Supli effendi (Warta Industri Hasil Pertanian, 2005)
The research is aimed at studying the effect of rotation mollen dryer and comparison sugar addition with noni pulp to the characteristic of noni juice microencapsulation (morinda citrifolia).The rotations of mollen dryer used are 24,30,and 36 rpm.Comparison sugar addition and noni pulp are 47%:41%,54%:34% and 60%: 28%.The result showed that analysis of the best product are obtained from rotation of mollen dryer 36 rpm comparison addition of sugar and noni pulp (60%:28%) that resulted in the lower mean value of like acceptability (taste ,flavor,colour,texture and interest visible) with water contend at 6,96% ,total sugar93,75% vitamin c 0,18 mg/100g ) and tss 86,70 %.